From comfort to climate action: exploring sustainable ergonomic awareness among school teachers in Terengganu, Malaysia - Alias, Ayuni Nabilah; Yaakub, Norwahida; Mustafa Udin, Nurulain; Mohamad Jamil, Putri Anis Syahira; Karuppiah, Karmegam (2025)
Aim: This study explores school teachers’ awareness, perception, and practices concerning sustainable ergonomic intervention products in Terengganu, Malaysia. Given the critical role teachers play in shaping environmentally responsible behaviours and influencing institutional procurement choices, promoting sustainable ergonomic awareness among educators could catalyse broader climate action within the school environment.